A COMPARATIVE STUDY OF ADVERBS IN ENGLISH AND UZBEK LANGUAGES - Sultonova Nodiraxom Erkinjon qizi (World Scientific Research Journal, 2025)
Annotation. This article presents a comparative analysis of adverbs in English and Uzbek, focusing on their grammatical functions, classification, and usage. It explores how both languages express manner, time, place, frequency, and degree through adverbs, while highlighting structural and functional differences. The study aims to deepen understanding of how adverbs operate in each language and to provide practical insights for learners, linguists, and translators working between English and Uzbek.